Analisis Efektivitas Program Preventive Maintenance Menggunakan Metode Total Productive Maintenance (TPM) di PT Sinar Sosro Cibitung - Purnamasari, Anita; Putra, Fibi Eko; Astuti, Retno Fitri (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study evaluates the effectiveness of the preventive maintenance program in the filling line of PT Sinar Sosro Cibitung by applying the Total Productive Maintenance (TPM) approach and measuring Overall Equipment Effectiveness (OEE). Data were collected through observations, interviews, and maintenance log documentation during September 2024. The analysis focused on three OEE components (availability, performance, and quality) and identification of the Six Big Losses. The results show that the average OEE value of the filling machine reached 92.0% (availability 94.3%; performance 98.5%; quality 99.3%), indicating performance above the world-class standard set by JIPM. The findings suggest strengthening the autonomous maintenance program and controlling production losses to ensure machine performance sustainability.